A Syntactic Analysis of Sentence Structure from Native Speaker Captions on Instagram Using Generative Transformational Grammar - Dinda Kholilah Saragih; Dedek Bayu Trinanda; Rahmawati Rahmawati; Mayasari Mayasari (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The aim of this research is to find out the type of sentences used in caption of native speakers on Instagram. And its sentence analyzes using the Noam Chomsky theory on which a tree diagram shows its structure. The type of sentences collected have been taken from caption by several foreign artists. The research also employed qualitative methods of analysis. The results of this research have been the 14 data collected from the caption. The data shows the 3 types of sentences found mostly on tables and tree diagrams. The table and tree chart process demonstrates that the significance of sentences can be clearer, so the substance of the story is conveyed effectively to the user.